HUMAN DICROCOELIASIS 2 CASE REPORTS FROM IRON - A.Sohrabi (Tehran University of Medical Sciences, 1982)
Dicrocoelium dendriticum is 10 by 2 mm. trematodes which live in the liver of the cattle, goats and sheep but it occasionally infects the human being. During the study of intestinal infections in the Caspian Sea region 2 cases of Dicrocoeliasis were found. The method for diagnosis was Formol-Ether concentration technique for stool examination. These two patients had eosinophilia and vague abdominal pains and digestive disorders. The following points are worthwhile to remind for the patients in the Caspian Sea region. 1. The Formol-Ether technique of stool examination is the best method for diagnosis of trematodes ova. 2. Those patients who come from the Caspian Sea region and have vague abdominal pain and esosinophilia should have a stool examination by the Formol-Ether technique. 3. In the differential diagnosis of ictrus and liver diseases one should remember the distomatosis.